PENGEMBANGAN ASESMEN KINERJA PRAKTIKUM BOTANI FANEROGAM BERBASIS KOMPETENSI PROSES SAINS - fajarwati, laras kurnia (Undiksha, 2021)
AbstractThis research uses research and development methods to develop the performance assessment of Fanerogam botany practicum. Development of instruments for students to measure psychomotor aspects. This study uses the 4 model which is a literature review (definition), design (design), development (development) and dissemination (disseminated) (Thiagarajan, 1974). In the development of performance assessment boterogram botany practicum was not carried out until it was distributed because it was concentrated with the existence of the covid-19 outbreak. The instrument developed in this study includes a performance appraisal sheet and a practical performance appraisal sheet which will be filled out by the validator. Based on the average validity score, the expert obtained the results of the development of botany lecture performance assessment instruments showing very valid criteria. Overall practical performance development instruments can be used to measure the psychomotor level of students when conducting botany Fanerogam practicums.